Analisis Faktor Sosial Ekonomi yang Mempengaruhi Upah Minimum Kabupaten/Kota di Provinsi Jawa Tengah Tahun 2017-2021 - Putri, Layli Lathifah Isnaini; Aisyah, Siti (Ekonomis: Journal of Economics and Business, 2024)
This study aims to examine the influence of socio-economic factors such as CPI, TPAK, GRDP, and per capita income on district/city minimum wages in Central Java Province from 2017 to 2021. The data used is secondary data with panel data from the Provincial Statistics Center Central Java. The linear regression analysis method was used with the Eviews 10 software. The study's results show that GRDP and per capita income have a big good effect on the minimum wage, while CPI and TPAK have a small effect. The government should maintain a good level of GDP growth and income per capita wage rates for workers in the Province of Central Java.